2016
DOI: 10.3390/inorganics4020017
|View full text |Cite
|
Sign up to set email alerts
|

Olivine-Based Blended Compounds as Positive Electrodes for Lithium Batteries

Abstract: Blended cathode materials made by mixing LiFePO 4 (LFP) with LiMnPO 4 (LMP) or LiNi 1/3 Mn 1/3 Co 1/3 O 2 (NMC) that exhibit either high specific energy and high rate capability were investigated. The layered blend LMP-LFP and the physically mixed blend NMC-LFP are evaluated in terms of particle morphology and electrochemical performance. Results indicate that the LMP-LFP (66:33) blend has a better discharge rate than the LiMn 1´y Fe y PO 4 with the same composition (y = 0.33), and NMC-LFP (70:30) delivers a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…There is thus scope for significant improvements to be made to LFP cathodes by carefully tuning the electrical properties of the electrolyte and the electrode conduction network, a fact that has been noted previously by Johns et al [25] who demonstrate that changes to the electrolyte properties in a LFP cathode can result in increases in maximum discharge rate of around two orders of magnitude. Volumetric energy density and rate capability can also be improved by using a blend of differently sized electrode particles [27,28,47]. Liu et al [28] showed that by using a nano-micro structured LFP electrode it is possible to achieve higher compaction density, lower resistance, superior rate capability, and higher volumetric energy density whilst still maintaining excellent cycling stability [28].…”
Section: Introductionmentioning
confidence: 99%
“…There is thus scope for significant improvements to be made to LFP cathodes by carefully tuning the electrical properties of the electrolyte and the electrode conduction network, a fact that has been noted previously by Johns et al [25] who demonstrate that changes to the electrolyte properties in a LFP cathode can result in increases in maximum discharge rate of around two orders of magnitude. Volumetric energy density and rate capability can also be improved by using a blend of differently sized electrode particles [27,28,47]. Liu et al [28] showed that by using a nano-micro structured LFP electrode it is possible to achieve higher compaction density, lower resistance, superior rate capability, and higher volumetric energy density whilst still maintaining excellent cycling stability [28].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the high thermal stability significantly improves the safety of the blend electrode. [25][26][27][28][29][30] Partial substitution of iron with manganese increases the energy density of the material, which enables both excellent electrochemical performance as well as low cost electrode when mixed with NMC. [29,30] The third binary combination, LMFP and LMO, is free of cobalt and nickel, which makes this blend inexpensive and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of phospo‐olivines such as LiFePO 4 also improve the rate capability of electrodes based on layered oxides. Moreover, the high thermal stability significantly improves the safety of the blend electrode [25–30] . Partial substitution of iron with manganese increases the energy density of the material, which enables both excellent electrochemical performance as well as low cost electrode when mixed with NMC [29, 30] .…”
Section: Introductionmentioning
confidence: 99%
“…Figure also indicates that NMC particles are fused together and form a macroporous structure. It is also reported that uniform distribution of particles can provide good the electrode‐electrolyte contact area and facilitating the transportation of Li + and electrons …”
Section: Resultsmentioning
confidence: 99%